Spot size characterization of focused non-Gaussian X-ray laser beams - Chalupský, J; Krzywinski, J; Juha, L; Hájková, V; Cihelka, J; Burian, T; Vysín, L; Gaudin, J; Gleeson, A; Jurek, M; Khorsand, A R; Klinger, D; et al. (Optics express, 2010)
We present a new technique for the characterization of non-Gaussian laser beams which cannot be described by an analytical formula. As a generalization of the beam spot area we apply and refine the definition of so called effective area (A(eff)) [1] in order to avoid using the full-width at half maximum (FWHM) parameter which is inappropriate for non-Gaussian beams. Furthermore, we demonstrate a practical utilization of our technique for a femtosecond soft X-ray free-electron laser. The ablative imprints in poly(methyl methacrylate) - PMMA and amorphous carbon (a-C) are used to characterize the spatial beam profile and to determine the effective area. Two procedures of the effective area determination are presented in this work. An F-scan method, newly developed in this paper, appears to be a good candidate for the spatial beam diagnostics applicable to lasers of various kinds.
Keywords: lasery; Models, Statistical; radiační rozptyl; Computer Simulation; světlo; normální rozdělení; Equipment Design; Lasers; počítačová simulace; rentgenové záření; statistické modely; analýza selhání vybavení; Light; design vybavení; Computer-Aided Design; design s pomocí počítače; X-Rays; Normal Distribution; Scattering, Radiation; Equipment Failure Analysis